Blacks, Reds, and Russians : sojourners in search of the Soviet promise - Carew, Joy Gleason (Rutgers University Press, 2008)
One of the most compelling, yet little known stories of race relations in the twentieth century is the account of blacks who chose to leave the United States to be involved in the Soviet Experiment in the 1920s and 1930s. Frustrated by the limitations imposed by racism in their home country, African Americans were lured by the promise of opportunity abroad. A number of them settled there, raised families, and became integrated into society. The Soviet economy likewise reaped enormous benefits from the talent and expertise that these individuals brought, and the all around success story became a platform for political leaders to boast their party goals of creating a society where all members were equal. In "Blacks, Reds, and Russians", Joy Gleason Carew offers insight into the political strategies that often underlie relationships between different peoples and countries. She draws on the autobiographies of key sojourners, including Harry Haywood and Robert Robinson, in addition to the writings of Claude McKay, W.E.B. Du Bois, and Langston Hughes. Interviews with the descendents of figures such as Paul Robeson and Oliver Golden offer rare personal insights into the story of a group of emigrants who, confronted by the daunting challenges of making a life for themselves in a racist United States, found unprecedented opportunities in communist Russia.